SCIENTIFIC ARTICLE ENTITLED THE EFFECTIVENESS OF SUSTAINABLE DEVELOPMENT ELEMENTS IN INSTITUTIONS - Hassanein Hadi Saeed (Scholars Digest Publishing, 2024)
In a rapidly changing competitive environment, a necessary condition for the successful operation of an organization is to ensure its sustainable development. The sustainable development of an organization is not only the ability of the organization to withstand the negative impact of the external environment, but also the effective use of limited resources. Ensuring the sustainable development of the enterprise is considered within the framework of the concept of corporate sustainability, and addresses the issues of rational combination of economic, environmental and social results of the organization's activities in order to maintain its competitiveness. The growing interpretation of the concept of corporate sustainability among various management styles is through the desire of organizations to maintain the achieved level of activity, gain competitive advantages over other organizations, enhance their economic potential, increase the well-being of stakeholders, as well as contribute to solving local community problems. One of the tools for achieving sustainable development for the organization is the integration of the quality management system based on quality standards. Thus, ensuring the sustainable development of an organization is a systematic solution to the problems of balanced social, economic and environmental development of the organization. At the same time, the introduction of the practice of sustainable development into the activities of the organization requires the formation of an appropriate mechanism and systematic support, and the solution of these tasks depends on the type of economic activity of the organization, the form of ownership, size and existing organizational conditions, standards of the external environment and other factors. The importance of work lies in the sustainability of the educational institution, from By taking into account all its aspects, such as: political, legal, economic, environmental, social, international and informational. Therefore, the question of improving the organization's management system based on the integration of requirements of standards in the field of sustainable development. The subject of the article includes knowing the elements of sustainable development for the founders through developing a comprehensive plan that includes assigning the following tasks
Keywords: Sustainable Development, Corporate Sustainability, Quality Management System, Environmental Management, Strategic Planning.